(untitled) (Revista Electrónica REDINE, 2018)
Validation of a competency profile includes the confirmation of the validity of the proposed features, according to the intentions and principles of the educational project. This paper describes the process of validation of professional profile based on competencies of the career of agricultural high technician at the Centroccidental Lisandro Alvarado University. The research is descriptive - correlational, the sample size was 75 people: 23 teachers, 16 employers, 20 students and 16 graduates. The results reveal a high degree of acceptance of both key purpose as the competencies of the professional profile. The minimum level of validity was high and correlations were significant, concluding that there is a reasonable agreement of respondents on key purpose, competencies and basic functions of the professional profile.